2021
DOI: 10.1039/d1cp01303c
|View full text |Cite
|
Sign up to set email alerts
|

A benchmark ab initio study of the complex potential energy surfaces of the OH + CH3CH2Y [Y = F, Cl, Br, I] reactions

Abstract: We provide the first benchmark characterization of the OH− + CH3CH2Y [Y = F, Cl, Br, I] reactions utilizing the high-level explicitly-correlated CCSD(T)-F12b method with the aug-cc-pVnZ [n = 2(D),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 54 publications
(73 reference statements)
2
22
0
1
Order By: Relevance
“…The mean absolute error (MAE) of MP2 and CCSD(T)/PP/t methods relative to experimental values are 5.1 and 4.0 kcal mol À1 , respectively. We noticed that Domokos et al 41 obtained similar values using MP2/aug-cc-pVDZ, similar to our MP2/ECP/d method, and their CCSD(T)-F12b/aug-cc-pVQZ (+ DZPE[CCSD(T)-F12b/aug-cc-pVDZ]) method gave values which are in excellent agreement with the experimental values.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The mean absolute error (MAE) of MP2 and CCSD(T)/PP/t methods relative to experimental values are 5.1 and 4.0 kcal mol À1 , respectively. We noticed that Domokos et al 41 obtained similar values using MP2/aug-cc-pVDZ, similar to our MP2/ECP/d method, and their CCSD(T)-F12b/aug-cc-pVQZ (+ DZPE[CCSD(T)-F12b/aug-cc-pVDZ]) method gave values which are in excellent agreement with the experimental values.…”
Section: Resultssupporting
confidence: 88%
“…We note that during the preparation of this manuscript, the Czako ´group carried out a benchmark study on the non-solvated HO À + CH 3 CH 2 X reaction using a high-level explicitly-correlated CCSD(T)-F12b method. 41 Therefore, a thorough characterization of the reaction PESs for the titled reaction HO À + CH 3 CH 2 X using the microsolvation model is of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“… b The relative energies of OH – + CH 3 CH 2 Cl reaction at CCSD­(T)-F12b/aug-cc-pVQZ level is from ref . …”
Section: Resultsmentioning
confidence: 99%
“…Besides, the ionic radii of the nucleophile show the following increasing order of F − (1. 26 28 that is, the nucleophile becomes bulkier following the order F − < Cl − < Br − < I − . Variation of the nucleophiles from F − to I − leads to the elongation of X−C α in RC2, which indicated that the ion−dipole complex becomes more weakly bonded.…”
Section: Entrance Channel Complexesmentioning
confidence: 99%
“…From a theoretical point of view, the potential energy, 21 reaction dynamics, 22–24 steric 25 and solvent effects, 26–28 and quantum scattering 29 have been studied using ab initio calculations by several research groups. For example, the effects of micro-solvation on the OH − + CH 3 I reaction were investigated using the direct dynamics simulation, 30 which demonstrated that while the S N 2 reaction dominated at all reactant collision energies, proton transfer to form CH 2 I − was found to dominate at higher collision energies.…”
Section: Introductionmentioning
confidence: 99%